A naive time of flight ranging scheme for wireless sensor networks. (8th May 2020) - Baba, Asif Iqbal; Wu, Fan; Ahmed, Tanvir
Recently wireless sensor network (WSN) applications have been in high demand. The key aspects of these applications is 'localisation'. Due to low energy and limited processing capability, many sensor nodes do not have any knowledge about their location, thus requires a method to get localised within a network. Nodes can be localised based on the measurements estimated using different techniques. In this paper, a naive time of flight (ToF) ranging measurement scheme is presented which minimises the error coming from low resolution clocks of the deployed nodes and removes the effect of clock drift on ranging measurements. The proposed scheme uses inter-arrival time of multiple ranging requests on the receiver side and uses solely the receiver node's clock to calculate the time of flight. The accuracy achieved with the proposed method is better than other existing approaches. The results demonstrate that the proposed scheme achieved the accuracy within 1m.